Reproductive and Seed Germination Characteristics of Woody Borreria (Diodia Ocimifolia) in a Plantation Ecosystem - Lim, Fang Woei (1997)
Woody borreria belongs to the subfamily Rubioidene in the family Rubiacene. It is a brush weed 1 to 1.5 m high and reproduces through seeds. A survey confirmed the presence of woody borreria in every state of Malaysia except Perlis, Kelantan and Penang Island where there were no respondents. In 1993, woody borreria infestations accounted for 4 to 18% of the areas planted with oil palm or rubber. Woody borreria adapts well to shade. The wet season appears to favour the emergence of its seedlings. The objective of this thesis was to study the basic characteristics of woody borreria in order to develop effective long-term weed management strategies. Eight experiments were conducted. The study on phenology and reproductive characteristics showed that woody borreria emerged at 7 days after sowing (DAS), produced flowers at 51 days after sowing, fruits at 7 to 14 days after flowering and capsules at 14 to 21 days after fruiting. At 226 DAS, plants grown in the open and under reduced light (36 % light transmission) produced 15,000 seeds per plant, while 9% light transmission, 6,500 seeds per plant and; 1% light transmission, less than 10 seeds.